Faktor-Faktor yang Mempengaruhi Pengirim Remitansi TKI Asal Bali di Amerika Serikat - Aprilliana, Dewi; Meydianawathi, Luh Gede (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Some Indonesian Labour (Indonesian Manpower) to send a portion of their income to the family's place of origin in the form of remittances. Remittances have a positive impact for the region of origin and government as well. There are many factors that determine the size of the remittances are sent back . This study aimed to ascertain the effect of the amount of income, consumption of Indonesian labor, the needs of families in the area of ??origin, the U.S. dollar exchange rate and shipping costs of remittances to the amount of remittances which are sent back by Indonesian labour from Bali who worked in the United States. The United States became a country with the most Indonesian labour from Bali in 2011. The data used are primary data obtained through interviews with 99 respondents observation Balinese migrants working in the United States were analyzed using multiple linear regression techniques. The results showed that the dependent variable is affected simultaneously by the five independent variables with the dominant influence of the variable indicated by the large amount of income remittances sent back by the workers Balinese who work in the United States. Partial amount of income positively and negatively affect workers consumption and both variables have a significant effect on the rate of five percent siginifikansi. Family needs a positive effect, the value of the U.S. dollar exchange rate and the cost of remittances negatively affect the value of remittances that are sent back and the third variable is not significant at the five percent level of significance.
Keywords: remitansi; pendapatan; TKI